Wallace Stevens : A Celebration (Book collections on Project MUSE., 1980)
Honoring the centennial of Stevens' birth, this volume presents original essays by many of Stevens' best-known critics. Also included are 128 previously unpublished lines that appear in the poet's From the Journal of Crispin"" (an early version of ""The Comedian as the Letter C""); three endings composed for ""A Collect of Philosophy""; the complete Adagia entries from Stevens' notebooks; and thirteen letters to business associate Wilson E. Taylor. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available